Perfil de citocinas e quimiocinas no sangue periférico de indivíduos com carga parasitaria baixa na infecção pelo Schistosoma mansoni - Vanessa Normandio de Castro (2016)
Schistosomiasis mansoni is a chronic disease and the prolonged and continuous exposure to Schistosoma mansoni antigens results in a deviation of the immune response. For the diagnosis in low endemicity areas, the Kato-Katz method is commonly applied, however, this method has low accuracy. This study aimed to characterize the cytokine and chemokine profile in individuals with extremely low parasite load, who were diagnosed positive with the saline gradient and/or Helmintex® methods, and compare the immunological profile with individuals diagnosed by the Kato-Katz method and with individuals repetitively negative by different stool exams. In the Municipality of Januária, Northern Minas Gerais, 197 residents from the rural area of Brejo do Amparo were examined by different parasitological methods. Among these individuals, blood samples of 174 residents were obtained for assessment of immunological markers, using commercially available sandwich ELISAs for the following markers: type 1 immune response (IL-1, IL-6, TNF-, IL-27, CXCL10), type 2 (CCL11, CCL17, IL-5 and IL-13), inflammatory Th17 (IL-17) and regulatory response (IL-10). The results showed that before treatment, individuals with extremely low parasitic load exhibited elevated concentrations of the type 1 marker IL-6 in the peripheral blood, indicating an active inflammatory process in this group. Chemokines, such as type 1 (CXCL10) or type 2 (CCL11 and CCL17) immune response markers were detected indifferently in the four analyzed groups. Therefore, an explicit immune modulation was not observed in the peripheral blood. Also, the concentrations of IL-10 as a regulatory marker were minimal and indifferent among groups. At post-treatment, an increase in CCL11 chemokine concentration was observed in all groups, when compared with pre-treatment levels. In general, infected individuals presented a tendency to decrease the type 1 inflammation markers after treatment and increase type 2 markers, which could be beneficial in case of reinfection.